Using YouTube Videos in Class To develop EFL Learners’ Vocabulary A Case of First Year Students at M’sila University - Imane BAIOU, Fatima DEHMECHE (My University, 2020)
Abstract The present srudyaims to verify the role of incorporating youtube videos into the EFL classes to improve the academic vocabulary level of EFL learners and also to raise teacher`s awareness on using this conventional tool in the teaching process.and be able to include ICT instruction in EFL classes. In this descriptive study, questionnaires were conducted for both EFL students and teachers. For students, the questionnaire was conducted to investigate their academic vocabulary performance when teachers used youtube as a tool in their lessons. As far as teachers, a questionnaire was conducted to investigate their awareness when using such material and to examine the extent of youtube clips usage among them. The results showed that this study confirms the effectiveness of using youtube videos as a teaching tool. Students showed a positive attitude towards the tool and recommended teachers to apply it more in their lesson explanation. Teachers also supported the use of such material and advised learners to use it outside the classrooms. Even though, they do not use it as regularly as needed.